Analisis Manajemen Risiko pada Pelayanan Satker pada KPPN Kupang Tipe A1 - Adha Adha; Minarni A. Dethan; Sarlin P. Nawa Pau (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2025)
Every organization needs risk management to control its risks, including the State Treasury Service Office. Risk control is an important part of management, so that organizational goals are achieved. The purpose of this study is to get an overview of minimizing or mitigating risks in Task Force Services at the Kupang State Treasury Service Office Type A1. The method used is a qualitative method with a descriptive approach. The results of the study based on ISO 31000:2008 show the analysis of risk management in Task Force Services at KPPN Kupang Type A1, namely Minimizing or Mitigating Risks in the Kupang KPPN Task Force Services, Determining the Risk Management Context in the Kupang KPPN Task Force Services, Identifying Risks in the Kupang KPPN Task Force Services, Risk Analysis in the Kupang KPPN Task Force Services, Evaluation of Risk Management in the Kupang KPPN Task Force Services, and Risk Management Management in the Kupang KPPN Task Force Services.